IGNAZ GOLDZIHER: KRITIKUS HADIS DAN KRITIKUS SASTRA - Lalu Turjiman Ahmad (Holistic al-Hadis, 2015)
Speaking of a scholar can not be detached from his/her contribution(s) to the dicipline he/she deals with. In modern ḥadîth criticism, Ignaz Goldziher is regarded as one of the most prominent scholar with a wide range of influence. Through his provokative writings, he inspires the rise of many responses which lively signs the development of the discipline among Muslims and Orientalists. Goldziher’s interests, however, do not only cover ḥadîth, but also extended to other Arabo-Islamic sciences, more particularly literature criticism with the focus on ancient Arabic poetry. In regard with the ancient Arabic poetry, he too has his great influence by which he deserves to be regarded as a prominent critic of literature.Keen studies on Arabo-Islamic sciences that Goldziher conducted allows him for always being reffered to by scholars. And so his carefull writings are considerred still relevant. On any account, what makes it possible for him to pose such reputations is because of his broad and extensive reading, including the earliest history of the Arabs and Islam from authoritative sources.